A linguistic study of sūraṯ Al-fātiḥaṯ and Al-baqaraṯ in the poetic book: “Taisīr fi ulūm al-tafsīr” by Badr Al-Dīn Al-Ghazziyy / Israa Ghanim Ahmed - Israa, Ghanim Ahmed (2014)

(untitled)
This thesis is focused on the linguistic aspects of the poetic interpretation of the holey Quran, entitled “ TAISĪR FI ULŪM AL-TAFSĪR” This manuscript is considered as one of the linguistic interpretations which involves Syntax, morphology, rhetoric and semantics as well as highlighting opinions and linguistic recommendations. This accounts for the significance of this research which aims to deduce the linguistic significance of understanding the Quranic texts. This poetic interpretation was chosen for being a manuscript interpreting the Quran in a systematic poetic style by one of the Muslim scholars for a book with various sciences in its interpretation. According to the descriptive methodology of this study, the material is presented and studied followed by the analytic study of the linguistic issues in the manuscript. This study investigates the linguistic issues in the first chapter of Al- Fatiha and thirty verses from the second chapter of Al- Baqara of the manuscript followed by analyzing the linguistic texts with respect to significant sources and works in this regard. The research comes with an introduction, seven chapters and a conclusion. The study finds out that Al-Ghizi uses a word and its morphology after explaining its meaning in the Quranic verse. He sometimes mentions variant opinions of interpreters and linguists on the verse and agrees with them at times, and argues against them at other times. He cares for each word, its type, root and rhyme. In his discussion, Al- Ghizi does not stop at one interpretation but dwells on the various probable perspectives, thereby enriching the language, broadening the horizons and conveying other meanings the expressions could bear without committing the mind to a single meaning only. Al- Ghizi has the ability to deduce various meanings for a single rhetoric expression, and in this he leans more for circumlocution or Itnab.